ESTIMATION PARAMETER FOR PARETO DISTRIBUTION USING LEAST SQUARE METHOD AND MAXIMUM LIKELIHOOD ESTIMATOR - MOHAMAD AYYARURRAHMAN (NIM : 10106058); Pembimbing : Drs. Sumanto, M.Com., ABY
Pareto distribution is commonly used as a model the distribution of income is not the greatest for the overall income distribution. The parameter k is usually called the Pareto distribution Pareto coefficient. It can be used as a characteristic differentiation of 50% of the highest income. In this thesis, the method of least squares, maximum likelihood estimator is used to estimate the Pareto distribution. To find out which is the best estimator, the average squared error (MSE) is used to compare the least squares method and the maximum likelihood estimator